Berpikir Kritis: Mendorong Introduksi dan Reformulasi Konsep dalam Psikologi Islam - Ahmad Sulaiman; Nandy Agustin Syakarofath (Faculty of Psychology Universitas Gadjah Mada, 2018)
Islam once triumphed as a great civilization with two main characteristics: an appreciation of science as well as submission to the value of Tawheed. Unfortunately, at present these characteristics seem not to belong to Islam. Various measurement data show that Muslim-dominated countries such as Indonesia, have low values in higher-order thinking skills such as creative thinking and problem-solving. As a solution effort, this paper attempts to reintroduce the concept of critical thinking in the body of the current Muslim community. The effort begins by showing how important critical thinking is in Islam, the relevance of Islam and critical thinking and the adaptation of current research in the frame of Islamic Psychology. The main implication of this paper is the importance of seeing the significance of all researchers, both Muslim researchers and outside Muslims, in the process of Islamizing the concept.